2015
DOI: 10.1039/c5cp02627j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of structure and enhancement of upconversion luminescence in NaLuF4:Yb3+,Ho3+ crystals

Abstract: A series of NaLuF4:Yb(3+),Ho(3+) nano/micro-crystals with different crystal structures were synthesized via a hydrothermal method using citric acid as a chelating agent. The influences of NaF content, Li(+) doping, reaction temperature and reaction time on the crystal structure and shape of the as-synthesized NaLuF4 crystals were systematically investigated. To the best of our knowledge, it is the first time to report Li(+) doped α-NaLuF4:Yb(3+),Ho(3+) nanocrystals and the phase transformation by introducing L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
(56 reference statements)
0
28
0
Order By: Relevance
“…NaLuF 4 -based UCNCs have been demonstrated to exhibit bright upconversion luminescence (UCL) [17,18,19,20,21,22,23,24] and show efficient five- and four-photon ultraviolet emissions under continuous wave excitation at 980 nm [25,26,27]. Despite recent success in synthesizing NaLuF 4 nanoplates or nanorods with size over ~30 nm using thermal decomposition method [28,29,30,31] or hydrothermal method [32,33,34,35,36,37,38], the ability to prepare uniform single crystal phase sub-10 nm NaLuF 4 UCNCs remains elusive. Moreover, doping of a high concentration of inert Gd 3+ ions (≥20%) was typically required to prepare small-sized monodisperse NaLuF 4 UCNCs with single crystal phase previously [17,39], thus delivering traits actually from an entity of Lu-Gd alloyed host.…”
Section: Introductionmentioning
confidence: 99%
“…NaLuF 4 -based UCNCs have been demonstrated to exhibit bright upconversion luminescence (UCL) [17,18,19,20,21,22,23,24] and show efficient five- and four-photon ultraviolet emissions under continuous wave excitation at 980 nm [25,26,27]. Despite recent success in synthesizing NaLuF 4 nanoplates or nanorods with size over ~30 nm using thermal decomposition method [28,29,30,31] or hydrothermal method [32,33,34,35,36,37,38], the ability to prepare uniform single crystal phase sub-10 nm NaLuF 4 UCNCs remains elusive. Moreover, doping of a high concentration of inert Gd 3+ ions (≥20%) was typically required to prepare small-sized monodisperse NaLuF 4 UCNCs with single crystal phase previously [17,39], thus delivering traits actually from an entity of Lu-Gd alloyed host.…”
Section: Introductionmentioning
confidence: 99%
“…4 shows the SEM images of the hydrothermal products synthesized at 120°C for different reaction times. According to the morphology evolution with increasing reaction temperature, it is concluded that the formation rate of nucleation and the crystal growth rate are expedited with raising the reaction temperature, which will result in the formation of products with a large scale 44 . When the reaction time is extended to 5 h, the bundle-like microstructures continue to grow into the fantails, which are composed of many thin and small microrods.…”
Section: Resultsmentioning
confidence: 99%
“…All samples were prepared based on our previously reported procedures 2224 . As for the synthesis of Y 3+ -absent α-NaLuF 4 :20%Yb 3+ , 1%Tm 3+ nanocrystals, 3 mmol of citric acid (2 M, 1.5 mL), 5 mmol of NaOH (4 M, 1.25 mL) and 10 mL of deionized water were mixed and stirred for 10 min.…”
Section: Methodsmentioning
confidence: 99%